La violencia intrafamiliar y de género. Una visión del caso colombiano (2020)
There is in Colombia a clear policy to face domestic violence and against women. It is possible to identify the following characteristics of the Colombian experience in this matter: it is based on international and national law as well as case law, it is developed from the national and territorial perspective, it recognizes victims as rights holders, it imposes obligations to society and it seeks to adopt an integral approach to the violence´s phenomenon. However, despite the existence of a clear, systematic, and determined policy to fight against domestic violence and against women, there are important limitations that affects its effective implementation, and, therefore, the achievement of the pursued objectives. These difficulties concern with the lack of budget, insufficient public servants properly trained, inefficient criminal prosecution, reduced effectivity of protection actions, limited articulation among authorities and a weak operation of Family Commissioners.